2016
DOI: 10.1371/journal.pone.0157734
|View full text |Cite
|
Sign up to set email alerts
|

Applying GIS and Machine Learning Methods to Twitter Data for Multiscale Surveillance of Influenza

Abstract: Traditional methods for monitoring influenza are haphazard and lack fine-grained details regarding the spatial and temporal dynamics of outbreaks. Twitter gives researchers and public health officials an opportunity to examine the spread of influenza in real-time and at multiple geographical scales. In this paper, we introduce an improved framework for monitoring influenza outbreaks using the social media platform Twitter. Relying upon techniques from geographic information science (GIS) and data mining, Twitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
96
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 13 publications
0
96
0
2
Order By: Relevance
“…AI is likely to become useful in public health and disease surveillance. ML applied to twitter found that Tweets could be a useful supplementary influenza surveillance tool and correlate well with official statistics . ML models have also been developed to classify suicide‐related communication on twitter .…”
Section: Population and Social Media Analysismentioning
confidence: 98%
“…AI is likely to become useful in public health and disease surveillance. ML applied to twitter found that Tweets could be a useful supplementary influenza surveillance tool and correlate well with official statistics . ML models have also been developed to classify suicide‐related communication on twitter .…”
Section: Population and Social Media Analysismentioning
confidence: 98%
“…These studies have explored the progression of natural disasters such as wildfires [29] and earthquakes [30]. The spatiotemporal analysis of Twitter content has also been used to track disease outbreaks and distribution [31,32].…”
Section: Related Workmentioning
confidence: 99%
“…They were also able to demonstrate the coastal effects, where being located on the east or west coast of the US predicts more geotag users. Allen et al (2016) in their work on using Twitter data for surveillance of influenza used census data to normalize tweet count for individual cities. Li et al (2013) used socio-economic and demographic data from American Community Survey (ACS) to compare Twitter and Flickr usage patterns across contiguous United States.…”
Section: Bias In Social Media Datamentioning
confidence: 99%